2017
DOI: 10.1002/ijc.30898
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer stem cells as last soldiers eluding therapeutic burn: A hard nut to crack

Abstract: Cancer stem cells (CSCs) are found in many cancer types, including breast carcinoma. Breast cancer stem cells (BCSCs) are considered as seed of cancer formation and they are associated with metastasis and genotoxic drug resistance. Several studies highlighted the presence of BCSCs in tumor microenvironment and they are accentuated with several carcinoma events including metastasis and resistance to genotoxic drugs and they also rebound after genotoxic burn. Stemness properties of a small population of cells in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 168 publications
(340 reference statements)
0
35
0
Order By: Relevance
“…2d). PCSCs are considered as the origin and driving force of prostate cancer progression and metastasis 26,27 . CSCs are enriched in non-adherent spherical clusters of cells, which are termed mammospheres 28 .…”
Section: Tams-secreted Ccl5 Promotes the Invasion And The Pcscs Subpomentioning
confidence: 99%
“…2d). PCSCs are considered as the origin and driving force of prostate cancer progression and metastasis 26,27 . CSCs are enriched in non-adherent spherical clusters of cells, which are termed mammospheres 28 .…”
Section: Tams-secreted Ccl5 Promotes the Invasion And The Pcscs Subpomentioning
confidence: 99%
“…7,8 The relevance of this tumor heterogeneity is linked to various hallmarks of cancer including drug resistance. [9][10][11][12][13][14] Macrophages are diverse cells that show distinct phenotypes depending on their anatomical location and activating stimuli. 15,16 In breast cancer, macrophages can comprise up to 50% of the TME.…”
Section: Introductionmentioning
confidence: 99%
“…Work by our group supports the connection between EMT and BCSCs by demonstrating that overexpression of the homeobox transcription factor, Six1, in a mammary gland-specific Six1-overexpressing transgenic mouse model increased the CSC pool while simultaneously producing tumors that exhibited a partial EMT phenotype (McCoy et al, 2009). Furthermore, several recent studies demonstrated that tumor-initiating ability of mesenchymal tumor-initiating cells was abolished when they were converted into epithelial counter parts (Avgustinova and Benitah, 2016;Chakraborty et al, 2016;Nilendu et al, 2018). These findings suggest contexts in which dynamic interplay between EMP and stemness can lead to distinct cancer cell populations with unique characteristics and activities.…”
Section: Cancer Stem Cell and Emt Plasticity In Breast Tumorigenesismentioning
confidence: 86%